In Stent Restenosis After Drug-Eluting Stent Implantation in a Patient with Polycythemia Vera: A Case Report - I Gusti Ayu Ratna Dewi; Tristi Lukita Wening; Sidhi Laksono Purwowiyoto (Journal of Agromedicine and Medical Sciences, 2023)
Polycythemia vera happened in people around 40-60 years old and mostly men. The criteria are total red blood cells â‰¥36 mL/kg in males, thrombocytosis, leukocytosis, and JAK2 mutation. We present a case of a 63-year-old male with unknown history of polycythemia vera who came to our hospital with acute STEMI anterior, he previously had done a coronary angiogram at another hospital thirteen days ago and found out that his previous drug-eluting stent (DES) was total in-stent restenosis in proximal. To prevent recurrent ischemia events, we replaced Clopidogrel with Ticagrelor and continue Aspirin. Keywords: drug-eluting stent; in-stent restenosis; polycythemia vera